Differences in antibody responses with rapid agglutination tests for the detection of rubella antibodies. - Chernesky, M A (1986)
Rapid agglutination tests (Rubaquick, Rubascan, and Rubacell) were used to screen sera (374 from immune and 124 from susceptible patients) for rubella immunity. Compared with enzyme immunoassay (Rubazyme) the erythrocyte agglutination assays (Rubaquick and Rubacell) were greater than 98% sensitive and 92 to 96% specific. The latex test (Rubascan) was sensitive (97.8%) and specific (96.8%) on undiluted serum but only 68.7% sensitive on serum diluted 1:10. Although the three rapid assays detected a substantial number of positive sera within 3 months of rubella immunization, a large number of variable responses were seen after infection with rubella. Analysis of discordant results suggests that these tests may be effectively used for immunity screening. The different individual assay results observed on low-titered sera or blood collected shortly after infection or immunization may not be comparable, because each assay has a different antigenic component on the agglutinin.